Predatory mites and the fungus Neozygites floridana associated with spider mites on soybean, in Rio Grande do Sul, Brazil - Roggia, Samuel; Guedes, Jerson Vanderlei Carús; Kuss-Roggia, Rejane Cristina Roppa; Vasconcelos, Geraldo José Nascimento de; Navia, Denise; Junior, Italo Delalibera (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to verify the occurrence of predatory mites and the fungus Neozygites floridana, associated with spider mites in soybean (Glycine max L.), in Rio Grande do Sul, Brazil. From 2003 to 2005, samples of soybean leaves from the most important soybean producing regions of the state were evaluated. These samples were collected from different positions of the plant and randomly in the field. The predatory mite species found were Neoseiulus anonymus, N. californicus, Phytoseiulus fragariae, P. macropilis, Proprioseiopsis cannaensis, and Galendromus annectens. The fungus N. floridana was widely distributed and occurred in all the spider mite species found: Mononychellus planki, Tetranychus desertorum, T. gigas, T. ludeni and T. urticae.